2021
DOI: 10.3390/polym13213621
|View full text |Cite
|
Sign up to set email alerts
|

Using Geopolymer Technology on Synthesizing Leucite Ceramics

Abstract: The aim of this study is to assess the process of synthesizing potassium-based geopolymers (KGL) into leucite ceramics with regard to five variables, namely, alkaline solution ratio (R), sintering time (S), calcining temperature (T), mixing time (M), and curing time (C). Under these conditions, the specimens were tested by the viscosity test, the mechanical properties test, X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM) to understand the geopolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…The reason for this rise in compressive strength was that the geopolymer melted at a higher temperature due to the low Na + diffusion coefficient at high temperatures. Meanwhile, the study by Hsieh et al [72] concluded that the structure became denser as the temperature rose, which was related to the potassium found in the alkali activator being dehydrated.…”
Section: Geopolymer Ceramicsmentioning
confidence: 99%
“…The reason for this rise in compressive strength was that the geopolymer melted at a higher temperature due to the low Na + diffusion coefficient at high temperatures. Meanwhile, the study by Hsieh et al [72] concluded that the structure became denser as the temperature rose, which was related to the potassium found in the alkali activator being dehydrated.…”
Section: Geopolymer Ceramicsmentioning
confidence: 99%
“…Researchers have paid much attention to the optimization of geopolymer binders and concrete compositions [13][14][15], the study of the physical and mechanical properties of concrete [16][17][18][19][20] and structures based on them [21], as well as various uses of the technology of geopolymer binders to obtain new materials [22]. At the same time, the authors touch upon topical environmental issues in the production of geopolymer concrete [23,24] and the problems of predicting the mechanical characteristics of finished materials, products, and structures using artificial-intelligence technology [25].…”
Section: Literature Review On the Research Topicmentioning
confidence: 99%
“…Lee and colleagues assessed the preparation of potassium-based geopolymers (KGL) into leucite ceramics and tested their structure and mechanical properties [ 16 ]. By taking into consideration alkaline solution ratio, calcining temperature (T), and sintering, mixing, and curing time, they tested the prepared specimens to better understand the geopolymerization reactions and the characteristics of the KGL network.…”
mentioning
confidence: 99%